Catchment and River Management in Graduate Teacher Education: A Case Study of Student Teacher Learning and Teaching in the Upper uThukela Valley, KwaZulu-Natal - Heath, Gavin Edward Craig (Rhodes University, Faculty of Education, Department of Education)
This study developed as a progressive focus on a design research process towards the inclusion of new environmental knowledge in teacher education. It is centred on the clarification of pedagogical content knowledge for the teaching of catchment and river management in Geography teacher education. The study was developed as a design research case study with three phases or iterations of experiential engagement and data collection during the teaching of Postgraduate Certificate in Education students at the University of KwaZulu-Natal where I lecture Geography Education. The study's iterative design was developed around pedagogical content knowledge refinement with curriculum knowledge analysis (phase 1) that was followed by lecture delivery and analysis (phase 2) and analysis of student engagement during fieldwork, and on teaching practice in rural classroom contexts (phase 3). Data and insights were generated across the successive stages of knowledge differentiation and teaching and learning interactions over time, and included reflection with students involved in the lectures, fieldwork and teaching practice programme. The analytical work covered a review of trajectories in new environmental knowledge, social-ecological systems, sustainability competencies, practice architecture and fieldwork pedagogy. This was done using three research lenses, namely social-ecological systems, social learning and practice architectures. All the design research and review processes served to develop, clarify and refine pedagogical content knowledge for sustainability-oriented teacher education. Thus the study conformed to the tenets of design-based research that was centred on clarification and review of pedagogical content knowledge that was carried into phases two and three. Research was focused at the nexus of pedagogical content knowledge and sustainability concerns that is necessary for the teaching of catchment and river basin management within a social-ecological systems perspective for integrated water resources management in South Africa and globally. The findings informed an illustrative model on how the research was carried out. Six design research insights and principles conclude the study and encapsulate the contribution it makes to new knowledge on how teacher education practice can be progressively aligned with new content knowledge teaching and the teaching of sustainability concerns. Specific findings in the form of six research insights indicated that the fieldworkbased teaching practice experience proved a successful learning crucible to develop sustainability competences. The cohort of student teachers passed their fieldwork teaching practice despite inadequate covering of foundational concepts in school and university. The teaching of a catchment management strategy case study was valuable in all three phases of research. A multi-contextual teaching and learning environment was successfully negotiated and navigated by the student teachers. The present Curriculum and Assessment Policy Statement does not speak to the reality on the ground, particularly in deep rural environments. A compulsory virtual Geography teacher training experience is recommended. Lastly, varied and broad responses to the noted multi-contextual challenges are needed in order to prepare and equip student teachers for the demands of the new environmental knowledge in the curriculum. Based on the groundwork provided by this study, there is scope for further research especially regarding the varied and broad responses to this new environmental knowledge in the curriculum.
Keywords: Geography-- Study and teaching (Higher) -- South Africa KwaZulu-Natal; Watershed management-- Study and teaching (Higher) -- South Africa KwaZulu-Natal; Pedagogical content knowledge; Environmental education -- South Africa KwaZulu-Natal; Teacher effectiveness -- South Africa KwaZulu-Natal; Curriculum and Assessment Policy Statement (CAPS)